Using data-driven learning activities to improve lexical awareness in intermediate EFL learners - Liya Xue (Taylor & Francis Group, 2021)
A large number of empirical studies have demonstrated the impact of lexical chunks on foreign language learning. However, reliable and efficient use of the lexical approach remains a problem. In this paper, a revised chunk teaching approach, based on Data-Driven Learning (DDL) activities and language awareness theory, is proposed and tested. Taking an action research approach, the effects of DDL activities on increasing the lexical awareness of intermediate EFL learners were investigated. A 16-week course, using the teaching pattern of EIODI (Expose-Identify-Observe-Discover-Internalize) along with recognition and production tasks, was used to teach 158 intermediate EFL first-year university students. Quantitative questionnaire data from an in-class survey and a university course assessment survey revealed that the learners increased their awareness of lexical chunks and developed positive attitudes toward this approach. In addition, they reported a positive impact on their English proficiency; claims were supported by a statistical comparison of Finals for College English Course test scores for the two succeeding academic years. This research highlights the importance of increasing learners’ language awareness and using effective DDL activities.